Função de demanda de alimentos com parâmetros variáveis: uma análise da região sul do Brasil - Ikehara, Hideharu Carlos; Brandt, Sergio Alberto (Semina: Ciências Exatas e Tecnológicas, 2004)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Lucida Sans Unicode"; panose-1:2 11 6 2 3 5 4 2 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-2147476737 14699 0 0 63 0; @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0pt; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 85.05pt 70.85pt 85.05pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> In this paper the transformation of variables analysis has been applied to estimate the demand for food. Aggregated data for the Southern Region of Brazil, collected in 1974, was used in the analysis. Results indicate that food demand is incomeinelastic (Ey - 0,39/) and this elasticity tends to decline as income rises. Elasticities calculated form arbitrary functional forms (linear, duoble-log and ratio semi-log) are at times more than 60 percent different from that calculated from the "appropriate" form. The empirical evidence further suggest that there are economies of size in food consumption for learger house holds.